Experimental study on the nonlinear behavior of bearing-type semi-rigid connections. (15th November 2019) - Movaghati, Sepehr; Abdelnaby, Adel E.
Highlights: Bearing-type bolts add flexibility to semi-rigid connections. Relative displacement between contact surfaces provides energy dissipation capacity. Slips at beam-angle contact surfaces cause fluctuations in moment-rotation curves. Slips in bearing-type bolted connection increase pinching effect under cyclic loading. Abstract: This paper investigates the effects of bearing-type deformations on the nonlinear response of beam-to-column bolted connections. To experimentally investigate these effects, a set of top-and-seat angle semi-rigid steel connections with the same size of wide flange beam but different angle sizes and beam bolt numbers were tested under monotonic and cyclic loadings. Using image processing techniques, the connection rotation and the beam horizontal displacement were measured and the contribution of slip at the contact surfaces to the overall connection rotational was measured. Bearing-type deformations increased overall connection flexibility and energy dissipation capacity in a manner that cannot be neglected in nonlinear analysis. Under monotonic loading, the test results revealed that the slip between the beam flanges and the angle legs dominated the bearing-type deformations and the ultimate connection rotation increased up to 19%. In cyclic loading tests, the bearing-type deformations increased the pinching behavior, added up to 41% to the energy dissipation capacity of the connections in the last cycles, and up to 35% to the ultimate connection rotation.